2011
DOI: 10.1007/s12117-011-9118-0
|View full text |Cite
|
Sign up to set email alerts
|

Human trafficking revisited: legal, enforcement and ethnographic narratives on sex trafficking to Western Europe

Abstract: In this paper we focus on the ways 'victims' and 'perpetrators' are imagined in the narratives on women who have been trafficked to West Europe for sexual exploitation. Three specific domains: international/national law, local law enforcement and ethnographic academic perspective are particularly important as they strongly influence political reaction to trafficking and describe the phenomenon from the perspective of the individuals concerned. In our analysis, an explanation of the diversity of the perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…Yet another disturbing trend in trafficking industry is the training of victims as future perpetrators. Nigerian women who were trafficked into Netherlands as domestic servants are trained to recruit girls from back in Nigeria to be victimized as sex slaves [30].…”
Section: The Global Slave Trade and Human Trafficking Around The Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet another disturbing trend in trafficking industry is the training of victims as future perpetrators. Nigerian women who were trafficked into Netherlands as domestic servants are trained to recruit girls from back in Nigeria to be victimized as sex slaves [30].…”
Section: The Global Slave Trade and Human Trafficking Around The Worldmentioning
confidence: 99%
“…According to Hughes [31], evidence gathered from reports compiled by non-governmental organizations in the former Soviet Union showed that Russia, Ukraine, and Belarus had the highest number of women recruited to so-called marriage agencies that sell out women for exploitation [31]. Those countries were followed by Kyrgyzstan, Kazakhstan, Latvia, and Uzbekistan [30]. Ghana, Nigeria, and Senegal are source, transit, and destination countries for trafficked women and children in West Africa [32].…”
Section: The Global Slave Trade and Human Trafficking Around The Worldmentioning
confidence: 99%
“…New clients only get the address of a sex worker at the very last moment. Recent research carried out in the Dutch city of Almere, where the number of legal brothels and escort clubs is small, suggests that prostitution has almost disappeared from the streets, whereas there are growing indications that home prostitution and cyber prostitution are on the increase (Oude Breuil et al 2011). Similar reports have recently come from other cities (Utrecht in The Netherlands; Ghent in Belgium) where hidden prostitution appears to be growing as a result of the popularity of the new social media, virtual escort clubs, and teleprostitution.…”
Section: Horizontal Mobility Of Sex Workersmentioning
confidence: 99%
“…Eastern European criminal organizations are often reported to be involved in the kidnapping, deceiving, and selling of young women for the purpose of exploiting and mistreating them in shabby brothels and window prostitution. The emphasis on repression in Dutch and Belgian law enforcement practices brings with it that police investigators are focused on catching and prosecuting perpetrators involved in complex and highly mobile transnational networks (Oude Breuil et al 2011). Several studies conducted from inside the world of prostitution based on participant observation and repeat interviews with sex workers, clients, and pimps (Bovenkerk et al 2006;Zaitch and Staring 2008;Siegel 2007) have provided us with more nuanced and detailed data about the relationship between prostitutes and their pimps, boyfriends, agents, employers, or "loverboys" (the terms vary according to the nature of the sex work).…”
Section: Transnational Mobility and Organized Crimementioning
confidence: 99%
See 1 more Smart Citation